The impact of tax audit in reducing the tax gap an analytical study of sample of banks listed in the iraq stock exchange - Professor. Dr. Rihab Bedoui; Researcher. Ahmed Najah Mohammed (Scholar Express Journals, 2024)
The subject of taxes and the variables associated with it are extremely important, whether on the practical or theoretical level. In its quest to cover part of its expenses by relying on tax revenues, the state faces a set of challenges represented by tax evasion and the resulting tax gap in general. Thus, tax auditing constitutes the tool with which the size of the tax gap can be reduced. Based on the above and by observing the trends of previous researchers towards studying the variables within the subject of the current study, the size of the company was relied upon as a measure of the quality of tax auditing, while the tax gap is the difference between what is actually paid and what should be paid by the taxpayer. The research sample is represented by 16banks listed on the Iraq Stock Exchange. While using correlation and regression analyses to test the research hypotheses by employing the Eviews program, the research reached the conclusion that tax auditing has a direct impact on reducing the size of the tax gap and what is reflected in this on increasing tax revenues that will enable the state to practice many functions whose expenses are covered by these revenues. On the other hand, those interested should intensify tax auditing practices on taxpayers
Keywords: Tax audit; tax gap